2018
DOI: 10.1177/1757975918767622
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a school-based health education model to prevent opisthorchiasis and cholangiocarcinoma in primary school children in northeast Thailand

Abstract: Infection with the liver fluke Opisthorchis viverrini is the major causative factor inducing cholangiocarcinoma in the Mekong region of Southeast Asia. Northeast Thailand has the highest incidence of this cancer worldwide leading to about 20,000 deaths every year. Infection with the liver fluke comes from eating raw or undercooked fish, a tradition in this area that can potentially be countered by education programs at school level. Here we develop a school-based health education model, based on protection mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…School-based health education has been advocated for prevention of many infectious diseases ( 90 ) as well as for OV and CCA ( 91 ). Based on our initial trial ( 92 ), a school-based curricula program was established through the Faculty of Education, Khon Kaen University (KKU), and included primary to secondary school courses as well as vocational study. This has been implemented in 31 schools in 3 provinces in northeast Thailand.…”
Section: Intervention and Solutionmentioning
confidence: 99%
“…School-based health education has been advocated for prevention of many infectious diseases ( 90 ) as well as for OV and CCA ( 91 ). Based on our initial trial ( 92 ), a school-based curricula program was established through the Faculty of Education, Khon Kaen University (KKU), and included primary to secondary school courses as well as vocational study. This has been implemented in 31 schools in 3 provinces in northeast Thailand.…”
Section: Intervention and Solutionmentioning
confidence: 99%
“…This is the way to improve health literacy for community people. Previous study showed enhancing knowledge and perceived self-efficacy could make concerning danger of eating raw fish and of developing cholangiocarcinoma (Laithavewat, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…No OVinfected Bithynia snails, the first intermediate host, were detected in the lake after six years of implementation [28]. Several studies in Thailand have also indicated a correlation between the self-efficacy application on the health education programme for preventing OV and CCA [12][13][14][15]. There is some critical evidence that public health programmes are beneficial: without behavioural modifying public health processes, 86% of the infection could relapse [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have presented models for behaviour modification and reducing CCA risk in northeast Thailand. Health education programmes for preventing OV and CCA by applying the self‐efficacy concept of Bandura [11] were designed in the Nakhon Ratchasima [12, 13], the Surin [14] and the Khon Kaen [15]. Moreover, a group process study was applied to change consumption behaviour causing OV infection risk in the Sakon Nakhon [16].…”
Section: Introductionmentioning
confidence: 99%